Analysing Reputational Risks In Malaysia’s Public Universities With Waqf Fund And The Way Forward - Ahmad Yani Ismail; Norhanizah Johari; Nazifah Mustaffha (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 10th Islamic Banking, Accounting and Finance International Conference 2022 (iBAF2022): “Future-Proofing for Business Excellence Through Islamic Banking, Accounting and Finance”/ Editors: Norhaziah Nawai, Khairil Faizal Khairi, Suhaila Abdul Hamid, Muhamad Azrin Nazri, Nur Ainna Ramli, Sumaiyah Abd Aziz, Mohd Adha Ibrahim, Syadiyah Abdul Shukor. 13th-14th September 2022 (Virtual Conference) Organized by: Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia